Faktor-faktor yang Mempengaruhi Keberhasilan Berwirausaha - Fibria Anggraini Puji Lestari (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
This research is to fnd out what affect a person who is successful in entrepreneurship. In this study was obtain from questionnaires distributed to student using multiple linear analysis with SPSS 19.00 for windows software.The result of this study showed that variables of interes and talent ( 0.199), motivation ( 0.388) and science ( 0.270) in influencing success entrepreneurship.